1992
DOI: 10.1111/j.1476-5381.1992.tb14382.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for postsynaptic mediation of the hypothermic effect of 5‐HT1A receptor activation

Abstract: (hyperphagia) = 0.0O0 mg kg'. This contrasts with the similar ED5o values for both the hypothermic (ED5 = 0.08-0.10 mg kg-') and hyperphagic (ED50 = 0.06-0.10mg kg-') effects of 8-OH-DPAT.5 The evidence obtained for mediation of the hypothermic response to 5-HTIA agonists by postsynaptic sites is relevant to the interpretation of the effects on it of antidepressant treatments and depressive illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Although Hillegaart (1991) obtained a decrease in temperature on direct injection of 8-OH-DPAT into the dorsal raphe in rats, the dose of 8-OH-DPAT used was high and diffusion to postsynaptic sites may have occurred. Several other studies (Hutson et al 1987;O'Connell et al 1992;Millan et al 1993) have now shown that the hypothermic effect in rats is postsynaptically located. Furthermore, although Goodwin et al (1987b) showed that the hypothermic effect in rats as well as in mice was reduced after electroconvulsive shock (ECS), at least two studies (Blier and Bouchard 1992;Gur et al 1997) have shown that the sensitivity of the 5-HT 1A autoreceptor in the rat dorsal raphe is unaltered by ECS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although Hillegaart (1991) obtained a decrease in temperature on direct injection of 8-OH-DPAT into the dorsal raphe in rats, the dose of 8-OH-DPAT used was high and diffusion to postsynaptic sites may have occurred. Several other studies (Hutson et al 1987;O'Connell et al 1992;Millan et al 1993) have now shown that the hypothermic effect in rats is postsynaptically located. Furthermore, although Goodwin et al (1987b) showed that the hypothermic effect in rats as well as in mice was reduced after electroconvulsive shock (ECS), at least two studies (Blier and Bouchard 1992;Gur et al 1997) have shown that the sensitivity of the 5-HT 1A autoreceptor in the rat dorsal raphe is unaltered by ECS.…”
Section: Discussionmentioning
confidence: 88%
“…8-OH-DPAT induces dose dependent hypothermia in rodents which is antagonized by stereoselective 5-HT 1A receptor blockade (Goodwin et al 1985a(Goodwin et al , 1987aHillegaart 1991). Although a presynaptic mechanism has been suggested (Goodwin et al 1985a(Goodwin et al , 1987aHillegaart 1991), the majority of the evidence indicates that the hypothermic effect of 8-OH-DPAT is mediated via postsynaptic 5-HT 1A receptors in the hypothalamus (Hjorth 1985;Hutson et al 1987;O'Connell et al 1992;Millan et al 1993). 5-HT 1A receptor stimulation also evokes ACTH and corticosterone release in rodents, via an effect on corticotrophin releasing factor in the paraventricular nucleus of the hypothalamus (Koenig et al 1987;Gilbert et al 1988;Haleem et al 1989;Bagdy and Makara 1994) and possibly through an action at the level of the pituitary as well (Chaouloff 1993).…”
Section: Serotonergic Receptors Of the 5-ht 1a Subtype Have Been Suggmentioning
confidence: 99%
“…From then on, several studies carried out in laboratory animals and humans used the 5-HT 1A -induced hypothermia to assess the responsiveness of the 5-HT 1A autoreceptor in different disease states and following administration of various types of psychotropic drugs. Although the majority of studies (Hutson et al 1987;O'Connell et al 1992;Hillegaart 1991;Millan et al 1993;Blier and Bouchard 1992;Stockmeier et al 1992) now indicate that this response in rats results from the activation of postsynaptic 5-HT 1A receptors, it is still claimed that it is presynaptically mediated in mice (Goodwin et al 1985). In humans, this issue had not been addressed.…”
mentioning
confidence: 99%
“…The pharmacology of this response has been well characterized, demonstrating that 8-OH-DPAT-induced hypothermia is mediated by activation of 5-HT 1A receptors (Millan et al 1997;Scott et al 1994;Thielen et al 1996). Although it has been suggested that 8-OH-DPAT-induced hypothermia in rats is mediated by presynaptic receptors (Goodwin et al 1987b), the majority of evidence supports the view that in rats, the hypothermic response elicited by 5-HT 1A receptor agonists is mediated by postsynaptic receptors (Bill et al 1991;O'Connell et al 1992;Millan et al 1997 and discussion therein). 5-HT 1A receptor-mediated hypothermia has been used to assess the sensitivity of 5-HT 1A receptors following a variety of antidepressant treatments (Goodwin et al 1987a;Hensler et al 1991), and has been proposed as a model to screen and identify novel 5-HT 1A receptor agonists and antagonists (Millan et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of these drug treatment paradigms was confirmed by measuring the binding of [ 3 H]-ketanserin to 5-HT 2A receptor sites in cortical homogenates, because all of these drug treatments have been shown to result in downregulation of 5-HT 2A receptor sites. The sensitivity of postsynaptic 5-HT 1A receptors was assessed in vivo by two behavioral measures, forepaw treading (Tricklebank et al 1984;Scott et al 1994;Thielen et al 1996) or hypothermia (Bill et al 1991;O'Connell et al 1992;Millan et al 1997) induced by acute injection of the 5-HT 1A receptor agonist 8-OH-DPAT. Because changes in 5-HT 1A receptor second messenger function have not been consistently reported to follow administration of antidepressants or 5-HT 1A receptor agonists (Sleight et al 1988;Varrault et al 1991;Newman et al 1992), we chose not to measure second messenger responses associated with 5-HT 1A receptor activation following 5-HT 2 receptor agonist or antagonist treatment.…”
mentioning
confidence: 99%